Genomic diversity within the haloalkaliphilic genus Thioalkalivibrio. - Anne-Catherine Ahn; Jan P Meier-Kolthoff; Lex Overmars; Michael Richter; Tanja Woyke; Dimitry Y Sorokin; Gerard Muyzer (PLoS ONE)
Thioalkalivibrio is a genus of obligate chemolithoautotrophic haloalkaliphilic sulfur-oxidizing bacteria. Their habitat are soda lakes which are dual extreme environments with a pH range from 9.5 to 11 and salt concentrations up to saturation. More than 100 strains of this genus have been isolated from various soda lakes all over the world, but only ten species have been effectively described yet. Therefore, the assignment of the remaining strains to either existing or novel species is important and will further elucidate their genomic diversity as well as give a better general understanding of this genus. Recently, the genomes of 76 Thioalkalivibrio strains were sequenced. On these, we applied different methods including (i) 16S rRNA gene sequence analysis, (ii) Multilocus Sequence Analysis (MLSA) based on eight housekeeping genes, (iii) Average Nucleotide Identity based on BLAST (ANIb) and MUMmer (ANIm), (iv) Tetranucleotide frequency correlation coefficients (TETRA), (v) digital DNA:DNA hybridization (dDDH) as well as (vi) nucleotide- and amino acid-based Genome BLAST Distance Phylogeny (GBDP) analyses. We detected a high genomic diversity by revealing 15 new "genomic" species and 16 new "genomic" subspecies in addition to the ten already described species. Phylogenetic and phylogenomic analyses showed that the genus is not monophyletic, because four strains were clearly separated from the other Thioalkalivibrio by type strains from other genera. Therefore, it is recommended to classify the latter group as a novel genus. The biogeographic distribution of Thioalkalivibrio suggested that the different "genomic" species can be classified as candidate disjunct or candidate endemic species. This study is a detailed genome-based classification and identification of members within the genus Thioalkalivibrio. However, future phenotypical and chemotaxonomical studies will be needed for a full species description of this genus.